STRATEGY IN WRITING IN CONSTRUCTING PARAGRAPH IN THE ESSAY AT UKI TORAJA - Judith Ratu Tandi Arrang; Yizrel Nani Sallata (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2018)
All the sentences in a paragraph should be organized well to support the main idea which is stated in one sentence called topic sentence. In fact, the sixth semesters students of English Department of Christian University of Indonesia Toraja can write an essay but the paragraph in the essay sometime still far from a good paragraph. It is still difficult for students to construct a good paragraph. This is caused by the lack of skill in constructing paragraph. The objective of this research is to produce teaching writing strategy based on the identified errors by Satayatam and Pongrat criteria (2008). This research is designed as quantitative descriptive research. The result of the analysis shows that using outline is the strategy developed based on the result.